Mengimplementasikan Metode Pendidikan Rasulullah SAW di MMU Ranuklindungan Grati Pasuruan - Nursaman, Nursaman (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2023)
This research concerns all efforts and efforts to study the educational methods of the Prophet Muhammad. How to implement it in various Islamic educational institutions, especially at Madrasah Miftahul Ranuklindungan Grati Pasuruan. Therefore, the author would try to collect as many references to the educational methods of the Prophet Muhammad as possible, both from what is implied from the Al-Quran, Al Hadith, as well as the works of Salafunas Sholih Ulama and Contemporary Ulama. However, it can be realized that it is certain that the educational methods of the Prophet Muhammad may not all be the same as there are many stories from his friends, perhaps only some of them with great hope of finding a bright spot in the educational patterns and methods of the Prophet Muhammad and his friends in the past. Rasulullah SAW's educational methods are widely used by Islamic educational institutions, because Rasulullah's education is an education that continues to be relevant and never gets old until now, wherever and whenever. Meanwhile, in this research method, the author uses a combined historical and descriptive approach. The results of this research are: descriptive of the pattern of Islamic education during the time of Rasulullah Muhammad SAW including: Specifications of Rasulullah's educational methods and how to implement Rasulullah's educational methods in various Islamic education, especially at MMU Ranuklindungan Grati Pasuruan. With the hope that the educational method of Rasulullah SAW will be a form of transformative solution to Islamic education today which is faced by various problems and differences in perspective, understanding and implementation of Islamic teachings.